2020
DOI: 10.3390/cells9071682
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Metabolism in the Regulation of Obesity/Type 2 Diabetes

Abstract: Obesity is a pathophysiological condition where excess free fatty acids (FFA) target and promote the dysfunctioning of insulin sensitive tissues and of pancreatic β cells. This leads to the dysregulation of glucose homeostasis, which culminates in the onset of type 2 diabetes (T2D). FFA, which accumulate in these tissues, are metabolized as lipid derivatives such as ceramide, and the ectopic accumulation of the latter has been shown to lead to lipotoxicity. Ceramide is an active lipid that inhibits the insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 115 publications
2
41
0
Order By: Relevance
“…In addition to the previously reported metabolites, we also identified several novel ones, including sphingosine. As the precursor of sphingosine-1-phosphate (S1P), sphingosine plays an important part in sphingolipid metabolism [ 47 ]. In vitro studies revealed that elevated levels of sphingosine could inhibit glucose uptake in muscle cells, while S1P could upregulate glucose-stimulated insulin secretion in pancreatic β-cells [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously reported metabolites, we also identified several novel ones, including sphingosine. As the precursor of sphingosine-1-phosphate (S1P), sphingosine plays an important part in sphingolipid metabolism [ 47 ]. In vitro studies revealed that elevated levels of sphingosine could inhibit glucose uptake in muscle cells, while S1P could upregulate glucose-stimulated insulin secretion in pancreatic β-cells [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Sphingosine-1 phosphate (S1P) is a sphingolipid mediator present at high levels in the plasma of healthy individuals, where it is believed to play an important role in maintaining vascular health. [5][6][7][8][9][10][11][12] Endothelium and erythrocytes contribute, primarily, to the plasma pool of S1P, and the apoM-component of high-density lipoprotein (HDL) is the major carrier in plasma. 5,13 Not surprisingly, S1P and HDL-bound S1P are reduced in pathologies or conditions associated with endothelial injury, including diabetes, [14][15][16][17][18][19][20][21] metabolic syndrome, 22 myocardial infarction, 20,21 sepsis, 23,24 in-stent restenosis, 25 and in coronary and peripheral artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The SphK1 and SphK2 effect on pancreatic β cell activity is believed to be antagonistic. Saturated fatty acids stimulate the SphK1/S1P axis by inhibiting lipotoxicity-induced β cell apoptosis ( 55 ).…”
Section: Sphingosine-1-phosphatementioning
confidence: 99%